2023
DOI: 10.3390/ijms24044042
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Transport Cycle of LAT1 and Interaction with the Inhibitor JPH203

Abstract: The large Amino Acid Transporter 1 (LAT1) is an interesting target in drug discovery since this transporter is overexpressed in several human cancers. Furthermore, due to its location in the blood-brain barrier (BBB), LAT1 is interesting for delivering pro-drugs to the brain. In this work, we focused on defining the transport cycle of LAT1 using an in silico approach. So far, studies of the interaction of LAT1 with substrates and inhibitors have not considered that the transporter must undergo at least four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Moreover, the Cu(His) 2 complex identifies a binding site close to the crucial residue for substrate gating, i.e., the F252 ( Figure 6 B), 2 the shortest contact being 2.87 Å, and matches the site of histidine binding previously described. 23 , 44 The Cu(His) 2 binding site is also not too far from residue K204, involved in the interaction with ATP 23 ( Figure 6 B). To deepen this aspect, the mutants F252A and K204Q were tested for their ability to mediate the transport of the Cu(His) 2 complex.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the Cu(His) 2 complex identifies a binding site close to the crucial residue for substrate gating, i.e., the F252 ( Figure 6 B), 2 the shortest contact being 2.87 Å, and matches the site of histidine binding previously described. 23 , 44 The Cu(His) 2 binding site is also not too far from residue K204, involved in the interaction with ATP 23 ( Figure 6 B). To deepen this aspect, the mutants F252A and K204Q were tested for their ability to mediate the transport of the Cu(His) 2 complex.…”
Section: Resultsmentioning
confidence: 99%
“…Transport assays were carried out in HBSS 24 h after transfection. After a triple wash with HBSS and the preincubation for 30 min with shaking, the test compound and JPH203 41 were dosed with 10 μM [3H]-leucine (probe substrate) at 10 μM to the corresponding apical compartments. The assay was performed in triplicate.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…LCMS (method 3): R t = 0.997 min; MS (ESIpos) m/z = 442.2 [M + H] + . methyl) -8-((2methylimidazo[2,1-b]thiazol-6-yl)methyl)-1H-purine-2,6(3H,7H)dione (41). 39 (50 mg, 0.093 mmol) was dissolved in 4 mL MeOH and 2 mL acetone was added, followed by 23.4 mg (0.37 mmol) of NaCNBH 3 .…”
mentioning
confidence: 99%
“…Indeed, a recent report by Bothwell et al suggested that LAT1 is a ‘harmonizer’ and not a driver of amino acid accumulation [ 11 ]. Other investigators have demonstrated the role of LAT1 in regulating mTOR [ 12 ] and how LAT1 uses different conformations to complete its transport cycle [ 13 ]. Due to its reversible modes, the uptake and export of radiolabeled leucine are accepted assays used to assess LAT1 function [ 14 ].…”
Section: Introductionmentioning
confidence: 99%